2020
DOI: 10.1186/s43008-020-00041-z
|View full text |Cite
|
Sign up to set email alerts
|

The Collection of Zoosporic Eufungi at the University of Michigan (CZEUM): introducing a new repository of barcoded Chytridiomyceta and Blastocladiomycota cultures

Abstract: We formed the Collection of Zoosporic Eufungi at the University of Michigan (CZEUM) in 2018 as a cryopreserved fungal collection consolidating the University of Maine Culture Collection (UMCC, or JEL), the University of Alabama Chytrid Culture Collection (UACCC), and additional zoosporic eufungal accessions. The CZEUM is established as a community resource containing 1045 cryopreserved cultures of Chytridiomycota, Monoblepharidomycota, and Blastocladiomycota, with 52 cultures being ex-type strains. We molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
(42 reference statements)
0
21
0
Order By: Relevance
“…The final classification of the OTUs' reference sequences was carried out by inserting them over phylogenetic placement into the fungal phylogenetic reference tree (Yarza et al, 2017). Prior to the insertion, the fungal reference tree was enriched by 254 fungal 18S rRNA gene sequences of the SILVA dataset SSURef_128 not yet present in the tree, by 210 reference sequences of so-far unrecognized soil-inhabiting order-level clades described by Tedersoo et al (2017) and by 79 sequences of newly identified basal fungal taxa (Seto et al, 2020;Simmons et al, 2020; and uploaded sequence data on INSDC accession numbers: KJ668047-KJ668085). After inserting the generated sequences, the tree was inspected for novel diversity clades formed by at least five OTUs represented by environmental sequences.…”
Section: Dna Extraction Sequencing and Bioinformaticsmentioning
confidence: 99%
“…The final classification of the OTUs' reference sequences was carried out by inserting them over phylogenetic placement into the fungal phylogenetic reference tree (Yarza et al, 2017). Prior to the insertion, the fungal reference tree was enriched by 254 fungal 18S rRNA gene sequences of the SILVA dataset SSURef_128 not yet present in the tree, by 210 reference sequences of so-far unrecognized soil-inhabiting order-level clades described by Tedersoo et al (2017) and by 79 sequences of newly identified basal fungal taxa (Seto et al, 2020;Simmons et al, 2020; and uploaded sequence data on INSDC accession numbers: KJ668047-KJ668085). After inserting the generated sequences, the tree was inspected for novel diversity clades formed by at least five OTUs represented by environmental sequences.…”
Section: Dna Extraction Sequencing and Bioinformaticsmentioning
confidence: 99%
“…We used the blastoclad Paraphysoderma sedebokerense isolate AZ_ISR (2019), considering it is the same TJ-2007a strain described in Hoffman et al [ 13 ], since it was isolated from the same host ( H. pluvialis ) and from the same place at Sede-Boker, Israel. The ITS sequence (GenBank MW336992) of our isolate is 99.7% identical to P. sedebokerense isolates FD61 [ 21 ] and JEL0821 [ 41 ]. After isolation, we maintained it in a pure culture and continuously subculture it on solid blastoclad growth media (BGM) in our laboratory [ 40 ].…”
Section: Methodsmentioning
confidence: 79%
“…In the last five years, the Spizellomycetaceae has also shown increased zoosporic variability with further sampling, isolation, and reevaluation, providing evidence for four more genera (Letcher and Powell 2018 ; Powell et al 2018a ). Though the Powellomycetaceae remains monophyletic in a large-scale phylogeny of the order (Simmons et al 2020 ), there is molecular evidence that the endogenous Spizellomycetale s could be split to separate Brevicalcar into its own family, though there is no noteworthy morphological feature, by light or electron microscopy, that would be indicative of this distinction. As convergent thallus morphology has done before, convergent ultrastructural evolution can mask these divergent lineages until an adequate technique is able to observe the differences.…”
Section: Species Conceptsmentioning
confidence: 99%